Bio-economy and agri-production : concepts and evidence - Bochtis, Dionysis (Academic Press, 2021)
Bio-economy and Agri-Production: Concepts and Evidence bridges the knowledge gap on sustainability and bio-economy aspects of agri-production over the last decade. It complements traditional aspects on the specific topic with advanced engineering and ICT approaches that have been recently applied in agri-business (e.g. knowledge-based agriculture) under the prism of sustainability and circular economy principles. Topics cover the circular economy in agri-business, lifecycle thinking, lean management, agri-chains, green production and waste management, and more. The book approaches aspects of sustainable bio-economy in agriculture in a holistic way, contributing to the development of integrated agricultural systems. Based on topics presented at the XXXVIII CIOSTA and CIGR V International Conference, and supplemented by targeted invited articles of key-scientists, this book recognizes that as technology advances, agricultural production management practices are now being called upon to address the need for sustainability in the bio-economy.